Robotic modeling and simulation of palletizer robot using Workspace5. - Mohd. Johari, Nory Afzan; Haron, Habibollah; Mohamad Jaya, Abdul Syukor (2007)
Employment of robots in manufacturing has been a value-added entity in a manufacturing industry. Robotic simulation is used to visualize entire robotic application system, to simulate the movement of robot arm incorporated with components consist in its environment and to detect collision between the robot and components. This paper presents result of a project in implementing a computer based model to simulate Okura A1600 palletizer robot. The application uses Okura A1600 robot for palletizing bags at the end of the production line and focuses on pick-and-place application. The project objective is to generate a computer simulated model to represent the actual robot model and its environment. The project simulates the robot's first four joints, namely as the Waist, Shoulder, Elbow and Waist and focuses on the position of the robot's end effector, regardless its orientation. Development of the model is using Workspace5 as a simulation tool. Two types of methodology are used, which are the methodology for developing the robotic workcell simulation model and the methodology for executing the robotic simulation. The output of the project will be a three-dimensional view of robot arm movement based on series of predefined Geometry Points, layout checking and robot's reachability by generating working envelope, collision and near miss detection, and monitoring on the cycle time upon completing a task. The project is an offline programming and no robot language is generated.